2014
DOI: 10.1111/jfb.12340
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Gobiidae larvae in a tropical Brazilian estuary, with particular emphasis on the use of size classes to categorize species guilds

Abstract: The structure and seasonal dynamics of larvae of the Gobiidae family in the Mucuri Estuary (Bahia, Brazil) were studied for nine consecutive years. Sampling was conducted at three stations in the lower estuary channel, between 2002 and 2010, in relation to season, day and night and tidal variations. A total of 5802 Gobiidae larvae, representing 15 taxa (12 species and three morphotypes), were collected in the Mucuri Estuary during this time. The highest mean ± s.d. density of fish larvae, 54·7 ± 79·8 larvae 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…This pattern has not been described before for Brazilian estuaries, generally dominated by Ctenogobius boleosoma (Coser et al, 2007;Marcolin et al, 2010;Gomes et al, 2014) or Microgobius meeki Evermann & Marsh, 1899 (Barletta-Bergan et al, 2002a).…”
Section: Variablesupporting
confidence: 57%
See 1 more Smart Citation
“…This pattern has not been described before for Brazilian estuaries, generally dominated by Ctenogobius boleosoma (Coser et al, 2007;Marcolin et al, 2010;Gomes et al, 2014) or Microgobius meeki Evermann & Marsh, 1899 (Barletta-Bergan et al, 2002a).…”
Section: Variablesupporting
confidence: 57%
“…In the Mucuri River estuary, in a similar study with the Gobiidae family, a higher number of species was identified, but over a larger sampling period (Gomes et al, 2014). It must be remembered that not all studies of fish fauna have used the same sampling method.…”
Section: Variablementioning
confidence: 94%
“…There have been studies of the population dynamics and diets of C. spixii and the southern kingcroaker Menticirrhus americanus (L. 1758) in the Caraguatatuba system (Turra et al ., ; Denadai et al ., ), detailed ichthyoplankton work in the Sao Paulo and Rio de Janeiro areas (Bonecker et al ., ; Castro et al ., ), further north, detailed studies of the food webs in the Paraibo do Sul Estuary (RJ) (Di Beneditto et al ., ; Kehrig et al ., ) and studies of the ichthyoplankton communities in the Baia de Vitoria Estuary (Espirito Santo) (Joyeux et al ., ) and in the Mucuri Estuary (Bahía) (Bonecker et al ., ), where Gomes et al . () also studied the structure and seasonal dynamics of larval Gobiidae for nine consecutive years.…”
Section: Review Of Research Results and Activities By Geographic Areamentioning
confidence: 99%
“…Apogonid larvae inhabit reefs of tropical and subtropical seas where they occur from the surface to depths of 300 m, depending on the species (Lara, ). Gobiidae larvae are found in a variety of freshwater and marine ecosystems, but are primarily associated with shallow and coral reef waters (Yeung & Ruple, ; Gomes et al ., ). Larvae of Bregmacerotidae are very common in ichthyoplankton studies, and can be found in neritic and oceanic waters (Hare et al ., ; Namiki et al ., ).…”
Section: Discussionmentioning
confidence: 97%